2018
DOI: 10.1542/peds.2017-4330
|View full text |Cite
|
Sign up to set email alerts
|

Uninterrupted Infant Sleep, Development, and Maternal Mood

Abstract: Contrary to the importance of total sleep duration, the association between sleeping through the night and development in early infancy remains unclear. Our aims were to investigate the proportion of infants who sleep through the night (6-or 8-hour sleep blocks) at ages 6 and 12 months in a longitudinal cohort and to explore associations between sleeping through the night, mental and psychomotor development, maternal mood, and breastfeeding. METHODS: At 6 and 12 months of age, maternal reports were used to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 52 publications
3
35
0
1
Order By: Relevance
“…3 Moreover, several studies have found that there is considerable interindividual variability in the age at which infants learn to sleep through the night and that this variability reflects a normal development of infant sleep physiology. 2,4 In studies of typically developing infants, the proportion of infants who do not sleep through the night naturally decreases with age. 4 Given the natural and considerable interindividual variability observed in the age of sleep consolidation attainment and the conflictual advice given by healthcare professionals, it would be meaningful to assess parental expectations about infant sleep consolidation.…”
Section: Infant Sleep Consolidation: a Preliminary Investigation Of Pmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Moreover, several studies have found that there is considerable interindividual variability in the age at which infants learn to sleep through the night and that this variability reflects a normal development of infant sleep physiology. 2,4 In studies of typically developing infants, the proportion of infants who do not sleep through the night naturally decreases with age. 4 Given the natural and considerable interindividual variability observed in the age of sleep consolidation attainment and the conflictual advice given by healthcare professionals, it would be meaningful to assess parental expectations about infant sleep consolidation.…”
Section: Infant Sleep Consolidation: a Preliminary Investigation Of Pmentioning
confidence: 99%
“…2,4 In studies of typically developing infants, the proportion of infants who do not sleep through the night naturally decreases with age. 4 Given the natural and considerable interindividual variability observed in the age of sleep consolidation attainment and the conflictual advice given by healthcare professionals, it would be meaningful to assess parental expectations about infant sleep consolidation.…”
Section: Infant Sleep Consolidation: a Preliminary Investigation Of Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Infant sleep training emerged in the 1950s and 1960s when the first wave of the school of behaviorism (FWB) in psychology was applied to infantcare. Yet high level evidence demonstrates no decreased night waking or reliably improved maternal mood scores as a result of FWB interventions, and no improvement in developmental outcomes (Price et al, 2012; Bryanton et al, 2013; Douglas and Hill, 2013b; Mindell and Lee, 2015; Price et al, 2015; Kempler et al, 2016; NHMRC, 2017; Pennestri et al, 2018).…”
Section: Biology-culture Mismatch In Very Early Life Generates Enviromentioning
confidence: 99%
“…Each of these may arise from, or be exacerbated by, a mismatch between popular sociocultural and clinical approaches, and infant biology. Health professionals report inadequate training in management of breastfeeding and unsettled infant behavior problems, and often recommend approaches which have been shown not to help, or may even worsen these problems, with associated deleterious effects on parent–infant biobehavioral synchrony (Price et al, 2012; Bryanton et al, 2013; Douglas and Hill, 2013b; Rimer and Hiscock, 2014; Mindell and Lee, 2015; Price et al, 2015; Blunden et al, 2016; Etherton et al, 2016; Kempler et al, 2016; Thompson et al, 2016; Gavine et al, 2017; NHMRC, 2017; Pennestri et al, 2018).…”
Section: Biology-culture Mismatch In Very Early Life Generates Enviromentioning
confidence: 99%